Vector Capacity Study: Changes of Aedes albopictus behaviour in response to human lifestyles and its strategy to maximizing fitness cost in transmitting dengue viruses. - Wan Musthapa, Wan Fatma Zuharah (Universiti Sains Malaysia, 2016)
Behaviour is an important factor as the key factor to predict Aedes mosquito potential hosts and later estimates the spreading of dengue transmission. A survey Jan in two sub-distinct areas, urban Sungai Dua and suburban Batu Maung, Penang indicated that the biting frequency of Aedes albopictus was associated with the human lifestyle in relation to light use, protection methods, and fogging operation. The Aedes mosquitoes biting time was difference in urban area at 8-12pm, whereas for sub-urban the highest frequency of biting was at 12pm-4am. Using CDC light traps and BG Sentinel, we trapped the mosquitoes outdoor and found no significant differences on the number of Aedes mosquitoes under light and dark conditions for both sub-distinct areas (P<O.05). However, higher number of Aedes collected using CDC light trap was between 12 pm till 4am, thus suggested the changes in biting time than usual normal behavior (at sunset; daylight biter). Due to high frequency of fogging in both areas, we analyzed the effects of common use insecticide on the Aedes mosquitoes and found out that this species is still susceptible to larvicide (temephos and Bt!), but had higher chances to develop resistance on permethrin adulticide with subsequent effects on their progeny. As conclusion, the behavior of Aedes mosquitoes has been changed according to our lifestyle and frequency of chemical used, with eventually no longer follows the norm behavior as expected.